Influence of Wake-Vortex Turbulence on the Flight Safety - Galović, Borivoj; Grozdanić, Berislav; Steiner, Sanja (Promet - Traffic&Transportation)
With the growing air traffic intensity, at some ai1ports weare more often faced with the fact that aircraft land or take offone after another. Since evety aircraft leaves a turbulent vortexbehind, which acts unexpectedly and is destabilising for theaircraft flying into it, the flight safety in such repeated landingsand takeoffs becomes questionable. Determining the minimumsafety time interval between the repeated operations becomesimperative and a limiting factor for some airports withhigh air traffic intensity. Unlike militaty flying, where crew istrained to fly in a group, in civil air traffic the crew is nottrained for such flying and on top of it mostly operate on largeaircraft, which produce very strong turbulent vortex. Additionalsophisticated equipment in new modem aircraft improvesnavigation, communication and steering of the aircraft, butdoes not insure it from flying into an invisible turbulent vortex.This paper discusses the vortex generation, its nature and fa ctorsthat influence its intensity and duration. The paper alsodeals with a model of calculating the probability of flying intoa turbulent vortex regarding time intetval of repeated opera tions,and influence of sophisticated equipment installed, onthe stability and flight safety of an aircraft. Conclusion underlinesthe need to standardise the minimum safety time intervalseparation between the repeated operations, with the aim ofimproving flight safety.